A study on the distribution of forest tree species and forest biodiversity busing hyperspectral and multispectral imagery in the University Research Forest Taxiarchis in Chalkidiki - Καμπούρη, Μαρία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2015)
The aim of the study is to show how satellite or aerial imagery can be used to estimate patches of high biodiversity for conservation and management purposes in a Mediterranean forest ecosystem. The present thesis investigates the effectiveness of identifying forest tree species through high spatial resolution multispectral satellite imaging, as well as hyperspectral satellite and aerial imagery. We used Landsat and GeoEye multispectral images, as well as CASI and Hyperion hyperspectral images over Taxiarchis University Forest in Chalkidiki, North Greece. The images were subject to pre-processing for the purpose of reducing noise and the number of spectral bands used, along with file size and processing time, without compromising accuracy. The transforms used for band extraction included the Principal Component Analysis (PCA), the Minimum Noise Fraction (MNF) and for band selection, band selection based on the correlation between the spectral signatures of the trees of interest. Masks were created from field sampling was used for defining tree species’ spectral signatures, as well as consequent accuracy estimation. Classification was object based and aimed mainly on the identification of tree patches, but also tree species in the case of the CASI imagery with resolution up to 2 m. After the best image in terms of classification accuracy and stability, processing time and suitability in incorporating a fuzzy analysis based on physiographic characteristics of tree distribution, was selected, a biodiversity index (Simpson’s Biodiversity Index) was estimated.